IMPLEMENTATION OF INMATE ACTIVITY MONITORING BRACELETS TO PREVENT ESCAPE IN CLASS IIB CIANGIR OPEN PRISON - Marlissa, Martial Tedi; Soge, Markus Marselinus (Politeknik Pengayoman Indonesia, 2024)
Escaping from correctional institutions is one of the problems of disrupting security and order, so it is necessary to consider implementing prevention, one of which is using prisoner activity monitoring bracelets. This research aims to determine the implementation of prisoner activity monitoring bracelets and the barriers to their use. This research uses qualitative research methods using interviews and observations and regulations as primary data. This research took place at the Class IIB Ciangir Open Prison and took place from April to October 2023. The use of monitoring bracelets was implemented based on legal grounds and has a useful mechanism for knowing the position of prisoners while carrying out independence development and preventing prisoner escapes. This is related to policy implementation theory and situational crime prevention theory. When using prison activity monitoring bracelets, some obstacles can affect the function of the bracelet, namely natural factors, damage to the device, and humans.